An integrated valorization of industrial waste of eggplant: Simultaneous recovery of pectin, phenolics and sequential production of pullulan. (December 2019) - Kazemi, Milad; Khodaiyan, Faramarz; Hosseini, Seyed Saeid; Najari, Zahra
Graphical abstract: Highlights: An integrated bio-refinery process was used to valorize eggplant peel waste (EPW). Simultaneous recovery of pectin (26.1%) and phenolics (20.2%) was optimized. EPW hydrolysates were used as carbon source in production of pullulan (16.8 g/L). Physicochemical analysis suggested good purity for pectin and pullulan sample. Antiradical activity of extract sample was comparable to ascorbic acid and BHA. Abstract: Based on a bio-refinery concept, the valorization of eggplant peel wastes (EPW) in the production of multiple value-added products was aimed. The acid-free extraction process was applied in the simultaneous recovery of pectin and phenolic compounds. The extraction variables were optimized by response surface methodology using a Box-Behnken design and the maximum yield of pectin (26.1%) and phenolic compounds (20.2%) was obtained in the extraction temperature of 90 °C, time of 90 min and liquid/solid ratio of 40 mL/g. After recovery of pectin and phenolic compounds from EPW, the solid leftovers were enzymatic hydrolyzed and the hydrolysates were used as a carbon source in the microbial production of pullulan by Aureobasidium pullulans. The produced pectin and pullulan were characterized through the chemical and structural features. The results of FT-IR and H-NMR analysis approved the predominant presence of these two polysaccharides in the isolated samples. On the other hand, the antioxidant activity of the recovered phenolic compounds extract was evaluated by DPPH and ABTS radical scavenging activity and reducing power assay.